Normal endometrial cells in cervical cytology: systematic review of prevalence and relation to significant endometrial pathology. - Canfell, K; Kang, Y; Clements, M; Moa, A; Beral, V (2008)
OBJECTIVES: To estimate the prevalence of normal endometrial cells (NECs) and the proportion of NECs associated with significant endometrial pathology in conventional and liquid-based cytology (LBC) cervical smears; and to assess the association between NECs and clinical symptoms in women with endometrial hyperplasia or carcinoma. METHODS: Systematic review of the literature and meta-analysis of prevalence and proportion data. The review was confined to studies reporting on NECs in smears from postmenopausal women or women aged 40+. RESULTS: A total of 22 relevant primary studies were identified from 1970 to 2007. The overall summary estimate for the prevalence of NECs in smears from postmenopausal women or women aged 40+ in all screening smears was 0.4% (95% CI 0.2-0.7%); this was 0.3% (95% CI 0.1-0.5%) and 0.9% (95% CI 0.5-1.4%) for conventional and LBC smears, respectively; P = 0.003 for difference. The overall estimate for the proportion of NECs associated with significant endometrial pathology was 7% (95% CI 4-10%); this was 11% (95% CI 8-14%) and 2% (95% CI 1-2%) for conventional and LBC smears, respectively; P < 0.001 for difference. In women with significant endometrial pathology, the presence of NECs in followed-up women was associated with abnormal uterine bleeding in 79% (95% CI 68-87%) of cases. CONCLUSION: Compared with conventional cytology, LBC may be associated with a higher prevalence of NECs but these are less likely to be associated with endometrial pathology. This finding might be explained by more consistent use of sampling instruments for LBC with better access to the endocervical canal or alternatively by changes over time, broadly coincident with the introduction of LBC, in the population in which NECs are reported. In followed-up women with NECs, most endometrial pathology is accompanied by symptoms, implying that a relatively smaller number of additional cases are identified through follow-up of asymptomatic women.